The textbook in school physical education: A vision of teachers - De Andrade, Heitor Rodrigues; Darido, Suraya Cristina [UNESP] (My University, 2011)
Nowadays, textbook has been recognized, to a significant portion of education experts, as a relevant material to education process. In the field of Physical Education the textbook's production and study became practically neglectful. The objective of this study was to evaluate the applicability of a basketball textbook, built specifically for this study, with five teachers of Physical Education. The methodology used was qualitative, the interview was a data collection instrument. The results pointed that teachers established a critical relationship against the textbook of basketball and they pointed advantages and disadvantages for its use in school context.
O livro didático na educação física escolar: A visão dos professores
Keywords: Process teaching/learning; School physical education; Textbook